2005
DOI: 10.1002/mds.20584
|View full text |Cite
|
Sign up to set email alerts
|

Is sphincter electromyography a helpful investigation in the diagnosis of multiple system atrophy? A retrospective study with pathological diagnosis

Abstract: Sphincter electromyography (spEMG) is often used as an ancillary test when multiple system atrophy (MSA) is suspected. Our aim was to determine the clinical features associated with spEMG being performed, the influence of the result on the final clinical diagnosis, and its utility as a clinical investigation. A retrospective audit of all cases in the Queen Square Brain Bank between 1989 and 2002 was performed. The clinical features and diagnostic accuracy were compared between patients in whom spEMG was perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 20 publications
1
30
0
Order By: Relevance
“…Therefore, a negative result cannot exclude a diagnosis of MSA. More recently, Paviour et al [39] reported that among 30 sets of clinical data and postmortem confirmation in MSA cases with a duration of more than 5 years, 24 (80%) had abnormal EAS-EMG, 5 (17%) had a borderline result, and only one had a normal EMG.…”
Section: Sphincter Emg In Autonomic Disordersmentioning
confidence: 96%
“…Therefore, a negative result cannot exclude a diagnosis of MSA. More recently, Paviour et al [39] reported that among 30 sets of clinical data and postmortem confirmation in MSA cases with a duration of more than 5 years, 24 (80%) had abnormal EAS-EMG, 5 (17%) had a borderline result, and only one had a normal EMG.…”
Section: Sphincter Emg In Autonomic Disordersmentioning
confidence: 96%
“…Although there has been some controversy surrounding this, a reasonable consensus view is that provided other causes of neurogenic sphincter damage have been excluded and the laboratory has a well de¢ned upper limit of normal, the ¢nding of severe and chronic reinnervation, that is prolongation of electromyographically recorded motor units, may be contributory in the diagnosis of MSA [Vodusek, 2001]. A retrospective study which looked at post mortem con¢rmed cases of MSA found that 80% had had an abnormal anal sphincter EMG [Paviour et al, 2005]. There were, however, insu⁄cient sphincter EMG data on patients who had died with con¢rmed idiopathic PD to do a speci¢city and sensitivity calculation for the test.…”
Section: Differential Diagnosis Of Pd In Patients With Urinary Incontmentioning
confidence: 99%
“…Although usually normal in PD, sphincter EMG abnormalities were described in three patients with pathologically confirmed PD, but the ON was not examined histopathologically in these cases 8. Unfortunately, sphincter EMG studies were not performed in our case.…”
Section: Discussionmentioning
confidence: 76%